2022
DOI: 10.3389/fpubh.2021.819123
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Air Pollution Exposure and Ischemic Heart Disease Mortality Among Elderly in High Aging Asian Economies

Abstract: In the epidemiological literature, the impact of environmental pollution on cardiac mortality has been well documented. There is, however, a paucity of evidence on the impact of air pollution exposure on ischemic heart disease (IHD) mortality among the Asian aged population. In response, this research seeks to investigate the degree of proximity between exposure to ambient PM2.5, household PM2.5, ground-level ozone (O3), and IHD mortality in the top seven Asian economies with the highest aging rates. This inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…There is growing evidence suggesting that exposure to these pollutants may raise the risk of cardiac events and associated mortality. It is estimated that the use of solid fuels in residences, mostly for cooking, causes more than 3.5 million early deaths per annum and approximately 110 million disability-adjusted life years (DALYs) ( 69 , 70 ). The effects of indoor air pollution on cardiac health and outcomes have received less attention in emerging Asian nations, although they use equivalent or more biomass fuel than industrialized countries, indicating higher levels of indoor air pollution and relatively higher CVD burdens ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence suggesting that exposure to these pollutants may raise the risk of cardiac events and associated mortality. It is estimated that the use of solid fuels in residences, mostly for cooking, causes more than 3.5 million early deaths per annum and approximately 110 million disability-adjusted life years (DALYs) ( 69 , 70 ). The effects of indoor air pollution on cardiac health and outcomes have received less attention in emerging Asian nations, although they use equivalent or more biomass fuel than industrialized countries, indicating higher levels of indoor air pollution and relatively higher CVD burdens ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present study sought to quantify the associations of HTN, diabetes mellitus, and high blood cholesterol with mortality from stroke, CHD, and pulmonary heart disease by using grey relational analysis (GRA) models. Traditional statistical approaches, such as logistic regression, are inefficient for depicting the relations between variables in the biomedical domain, because of its dependency restrictions [15][16][17]. The grey relational models may overcome this shortcoming as they are devoid of assumptions.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of epidemiological literature shows that PM 2.5 is a well-defined risk factor for IHD, earlier studies of long-term PM 2.5 exposure focused more the United States and Europe, [11][12][13] whereas in the past decade more studies have been published in Asia and Oceania. 14,15 While there was an evidence-based metaanalyses also revealed that long-term exposure of PM 2.5 may be related to a higher risk of cardiovascular disease event. 16 However, the results were still limited and unclear.…”
Section: Introductionmentioning
confidence: 99%